Successful treatment of pachydermoperiostosis patients with etoricoxib, aescin, and arthroscopic synovectomy: Two case reports. Issue 47 (November 2017) - Zhang, Hengyan; Yang, Bo
Abstract: Rationale: Pachydermoperiostosis (PDP) is a rare hereditary disorder that affects the skin and bones. PDP is characterized by periostosis, digital clubbing, and pachydermia. Previous studies demonstrated that increased prostaglandin E2 (PGE2) levels resulting from defective protein degradation pathways play a crucial role in PDP pathogenesis, and males were more commonly and severely affected than females. Moreover, nearly all PDP patients suffer from refractory arthralgia. Although several different treatment modalities are used for PDP, therapy for this disease remains challenging. Patients concerns: Two cases of PDP showing symptoms consistent with polyarthritis and arthralgia that mainly affected the knees and ankles. Diagnoses: The diagnostic criteria for PDP include digital clubbing, periostosis, and pachydermia. The 2 patients were diagnosed as PDP based on the finger clubbing, facial cutis furrowing, knee and ankle arthritis, and radiographic evidence of periosteal proliferation. Interventions: Patient 1 had massive joint effusion that was treated by oral administration of etoricoxib and aescin combined with arthroscopic synovectomy, whereas Patient 2 had mild joint swelling and accepted only oral medication. Outcomes: Clinical symptoms of the 2 patients greatly improved after the treatment. During the 1-year follow-up, the patient experienced no adverse effects or recurrence. Lessons: The therapeutic results showed that oral etoricoxib could reduce inflammation and retard progression of pachydermia, or even relieve facial skin furrowing, but had limited efficacy for arthralgia. However, oral aescin had satisfactory efficacy for arthralgia. Thus, etoricoxib combined with aescin is a safe and effective treatment for PDP. Meanwhile, arthroscopic synovectomy can be used to treat joint effusion, but had no therapeutic effect on arthralgia. Therefore, postoperative oral medications would be needed as subsequent therapy for joint problems. In conclusion, this study proposes an effective and safe treatment plan to address symptoms experienced by PDP patients.